Analysis of the Spatial Distribution Pattern of the Urban Landscape in the Central Plains under the Influence of Multiscale and Multilevel Morphological Geomorphology - Hongxiang Li; Ting Zhao; Nan Ge (Complexity)
This paper presents an in-depth analysis and research on the spatial distribution pattern of the urban landscape in the Central Plains digital landscape form and proposes an optimization scheme. Based on the basic theories of systematics and complexity, this paper analyzes the self-similar characteristics of urban morphology, establishes the concept of schema, and constructs a multiscale and multilevel morphological map research framework by drawing on the “planar pattern” morphological analysis method of the school and the “matrix, patch, and corridor” spatial expression model of landscape ecology. The framework of morphological map research at multiple scales has been established, and the theory and method of describing, understanding, judging, and analyzing morphological evolution have been formed. Cities have self-similarity at different scales, and urban evolution is a process of recursion from small-scale hierarchy to large-scale hierarchy, and hierarchy is a phenomenon presented by the natural evolution of cities. After any morphological process is completed, it can only be transformed into the other two ways, so the static morphological description can be transformed into dynamic morphological process analysis.